2010
DOI: 10.1111/j.1741-6787.2009.00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Review of Technology and Dietary Assessment

Abstract: Six technology-based methods for dietary assessment were identified. Findings from validity and reliability testing of technology-based methods are encouraging and need replication. Clinically important features offered through technology may reduce reporting burden and offer behavioral feedback to users. Methodologically sound, empirical research into using technology-based application for dietary assessment in a variety of populations of sufficient size is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Technology allows food diaries to work interactively. [11][12][13][14] Food diaries can be programmed with individuals' online input and are designed to include functions such as food nutrient value reports, energy and nutrient problem identifiers, unhealthy food identifiers, and meal plan designs. 15,16 They can serve as cognitive tools that provide instant dietary evaluations to the individual.…”
Section: Introductionmentioning
confidence: 99%
“…Technology allows food diaries to work interactively. [11][12][13][14] Food diaries can be programmed with individuals' online input and are designed to include functions such as food nutrient value reports, energy and nutrient problem identifiers, unhealthy food identifiers, and meal plan designs. 15,16 They can serve as cognitive tools that provide instant dietary evaluations to the individual.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of epidemiological or complex multifactorial diseases is essential to take into account the gen*diet interaction because of the importance of nutrition in human beings and because dietary factors are linked to 4 of the 10 leading noncommunicable causes of death: cardiovascular disease, some cancers, stroke, and type 2 diabetes [1].…”
Section: Introductionmentioning
confidence: 99%
“…They presented the most used tools in US and Europe (without a wide review of related works) providing a description from the point of view of a user or researcher in nutrition. Long et al [1] presented a review of the evidence on the effectiveness of technology-based methods for dietary assessment by reporting six technology-based methods. Ngo et al [41] give a short review of computerized nutrition questionnaires and outlines some innovative methods for automating questionnaires, such as smart cards, personal digital assistants (PDAs) and mobile phones.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional use of either of these technologies, that is, for verbal person-to-person communication would have been captured as telephone-based trials; however, this detail was also not presented in the studies identified. It is suspected that given the time period of the studies captured in this review a growing use of portable technologies including cellular/mobile (Six et al, 2010) or smart phones (Long et al, 2010) may be seen in food-based RCTs beyond 2010 drawing on the various functionalities including short message service (Anhoj and Moidrup, 2005), voice recording (Rollo et al, 2011), and photographic image capture (Boushey et al, 2009) as validity and acceptance of such methods grows amongst both researchers and their participants. Information technology use in food-based RCTs is expected to increase in the future allowing automation of dietary analysis and also allowing other forms of assessment to be used efficiently.…”
mentioning
confidence: 99%